Hubungan Sistem Lymphe Dan Vena Pada Bagian Superficial Jantung - Djaka Prakosa Djaka Prakosa (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1974)
18 cow hearts have been studied to demonstrate the existence of communications between lymph vessels and veins on the superficial surface of the heart. The findings showed that in 9 cases such communications could be demonstrated, being 1 or 2 in number on each heart. Most of them were located on the sternocostal surface, especially near the apex.The diameters of the lymph vessels near the communications were found to be 80 to 480 microns.These anastomosis were assumed to play a role in certain conditions such as in lymphatic or venous stasis.